2021
DOI: 10.1186/s12883-021-02270-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term complications after stent assist coiling dependent on clopidogrel response

Abstract: Background Dual antiplatelet therapy (DAPT) is necessary for stent assisted coiling. However, long term use of DAPT has a potential risk of hemorrhagic events. We aimed to examine the relationship between clopidogrel reactivity and complications. Methods Patients who underwent stent assisted coiling for unruptured aneurysms or previously treated aneurysms and received periprocedural DAPT in our institution between August 2011 to March 2020 were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…10) Multiple reports have been made on postoperative antiplatelet therapy in the neurointerventional field. 4,[11][12][13][14] These studies have demonstrated the importance of postoperative platelet function tests. Kim et al examined the optimal duration of postoperative DAPT.…”
Section: Discussionmentioning
confidence: 96%
“…10) Multiple reports have been made on postoperative antiplatelet therapy in the neurointerventional field. 4,[11][12][13][14] These studies have demonstrated the importance of postoperative platelet function tests. Kim et al examined the optimal duration of postoperative DAPT.…”
Section: Discussionmentioning
confidence: 96%
“…It is important to note that the use of SAC in ruptured aneurysms is known to be associated with a greater risk of complications -often attributed to the use of dual antiplatelet therapy -and, according to several authors, should generally be avoided in such populations [47][48][49][50]. In this context, a recent meta-analysis investigating morbidity and mortality in SAC-treated unruptured intracranial aneurysm with wide necks, demonstrated an estimated pooled rate of mortality and overall neurologic complications to be 0.02% and 4.33%, respectively [36].…”
Section: Clinical Utility Of Sac For Intracranial Aneurysmsmentioning
confidence: 99%
“…12) Although it is common to continue to use DAPT for six weeks to six months, little research has been conducted on the proper length of DAPT use. 2)13)17)18) 20) In addition, few studies have been conducted on MAPT discontinuation. It is a common recommendation to maintain MAPT for the rest of one's life after SACE.…”
Section: Introductionmentioning
confidence: 99%